Factors Influencing The Behavior of Pregnant Women in Triple Elimination Screening - Muda, Iskandar; Erika, Erika; Khemkhaeng, Chalermchai (Jurnal Kebidanan, 2025)
Pregnant women are a vulnerable group to sexually transmitted infections such as HIV/AIDS, hepatitis B, and syphilis, which can have serious effects on both maternal and fetal health. These infections can be vertically transmitted from mother to baby, potentially leading to premature birth, low birth weight, congenital defects, or neonatal death. The objective of this systematic review is to identify the factors influencing pregnant women’s behavior in undergoing triple elimination screening. The databases used were PubMed, Science Direct, and Google Scholar. The keywords employed were factors influencing the behavior of pregnant women in triple elimination screening. A total of 7 articles were obtained from the literature search. The search results were filtered using the PICO framework and the CRAAP method. The study identified five factors influencing the behavior of pregnant women in triple elimination screening, namely: the role of healthcare providers, information sources, family support, utilization of prenatal classes, and maternal age. This analysis concludes that five factors influence the behavior of pregnant women in triple elimination screening: the role of healthcare providers, information sources, family support, utilization of prenatal classes, and maternal age. However, further research is needed to explore additional factors that may affect the behavior of pregnant women in triple elimination screening.